High Prevalence of blaNDM Variants Among Carbapenem-Resistant Escherichia coli in Northern Jiangsu Province, China - Bi, Ruru; Kong, Ziyan; Qian, Huimin; Jiang, Fei; Kang, Haiquan; Gu, Bing; Ma, Ping (Frontiers in Microbiology, 2018)
The continuous emergence of carbapenem-resistant Escherichia coli (CRECO) presents a great challenge to public health. New Delhi metallo-lactamase (NDM) variants are widely disseminated in China, so the research on the prevalence and transmission of diverse blaNDM variants is urgently needed. In the present study, 54 CRECO isolates were collected from 1185 Escherichia coli isolates in five hospitals in Northern Jiangsu Province, China from September 2015 to August 2016. Antimicrobial susceptibility tests, PCR detection of resistance determinants, multi-locus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were performed to characterize these strains. Plasmid conjugation experiments were carried out to determine the transferability of resistant genes from selected isolates. PCR-based replicon typing (PBRT), S1 nuclease-PFGE and Southern blotting were conducted for plasmid profiling. Carbapenemase genes were detectable in all CRECO isolates, among which thirty-one CRECO isolates were found to carry blaNDM-5 (54.7%), while, blaNDM-1, blaNDM-7, blaNDM-4, blaNDM-9, and blaKPC-2 were identified in fourteen, five, two, one, and one isolate, respectively. MLST results revealed 15 different STs and four new STs were first reported to be linked with NDM-producing isolates. PFGE typing showed that no more than two isolates with the same ST appeared to the same band pattern except three ST410 isolates. Twenty-six selected NDM-producing isolates were successfully transferred to E. coli J53 by conjugation experiments. Notably, 50.0% (13/26) of blaNDM variants were found to be carried by ~55 kb IncX3 plasmid. Our study reported a high prevalence of blaNDM variants, especially blaNDM-5, in Northern Jiangsu province, China. Diverse blaNDM variants were mainly carried by ~55 kb IncX3 plasmids, suggesting that the fast evolution and high transferability of this kind of plasmid promote the high prevalence of blaNDM variants. Therefore, large-scale surveillance and effective infection control measures are also urgently needed to prevent diverse blaNDM variants from becoming epidemic in the future.